Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
v * w = (3i - 2j) *(-i + 5j) = 3(-1) + (-2)(5) = -3 + -10 = -13
Hope that helps!
Answer:
v.w = -13
Step-by-step explanation:
v.w = (3i - 2j).(-i + 5j) = 3 × -1 × i.i + 3 × 5 × i.j + -2×-1 × j.i + -2×5 × j.j
i.i = j.j = 1 , i.j = j.i = 0
→
v.w = -3 - 10 = -13
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.